PKM JANTUNG PISANG CAMILAN SEHAT IBU MENYUSUI - Afiah; Syafriani; Nia Aprilla (COVIT (Community Service of Health), 2022)
Banana is one of Indonesia's leading commodities. Harvested area and banana production always occupy the first position. In 2012 the total production was 6,189,043 tons and the banana harvested area in Indonesia reached 103,157 hectares, with a productivity of 59.99 tons/ha. Indonesia itself is the fourth largest banana producing country in the world. Banana flowers have many health benefits, including high fiber content, low protein and fat, and a source of minerals such as magnesium, iron and copper. Dietary fiber is known to be useful for lowering blood cholesterol levels, normalizing blood glucose and insulin levels so that it is good for consumption by people with diabetes mellitus. In addition, banana heart has a very high antioxidant activity, most of which comes from anthocyanin compounds which are included in the flavonoid and polyphenol groups. The purpose of this activity is to explore innovative ideas, increase creativity, instill an entrepreneurial spirit, train mentally and teach to work hard and be responsible. In addition, another goal is to reduce the waste generated by processing them into banana heart chips and banana heart chips. There are several obstacles faced, namely (1) Limited capital. (2) Low motivation for entrepreneurship with banana heart as the main ingredient. (3) There is no diversity of banana heart products. (4) There is no packaging and marketing of banana blossoms. Keywords: various processed banana heart, marketing and income